An Education in Facebook? Higher Education and the world's largest social network - Kent, Michael; Leaver, Tama (Routledge, 2014)
An Education in Facebook? examines and critiques the role of Facebook in the evolving landscape of higher education. At times a mandated part of classroom use, at others an informal network for students, Facebook has become an inevitable component of college life, acting alternately as an advertising, recruitment and learning tool. But what happens when educators use a corporate product, which exists outside of the control of universities, to educate students? An Education in Facebook? provides a broad discussion of the issues educators are already facing on college campuses worldwide, particularly in areas such as privacy, copyright and social media etiquette. By examining current uses of Facebook in university settings, this book offers both a thorough analytical critique as well as practical advice for educators and administrators looking to find ways to thoughtfully integrate Facebook and other digital communication tools into their classrooms and campuses.